Accounting for business combinations: (Un)desirable uniformity? - Ribeiro, Humberto (2005)
For many years, two methods existed alongside each other in the USA to account for business combinations: the pooling of interests method, applied to operations, such as mergers, that met all the conditions as stated at APB Opinion No. 16; and the purchase method for all other combinations. This dual accounting status was also widespread through many other countries, although some included substantial GAAP differences (e.g. USA versus UK) or applied restrictions to the application of those methods. The 1998 G4+1 Position Paper concerning business combinations recognized the inconvenience of this diversity in accounting and recommended the use of a single method, preferably the purchase method. Following a long period of discussion and controversy, as is usual when the business combinations topic is on the table, FASB published in 2001 the SFAS No. 141, which confirmed the purchase as the unique method for business combinations accounting. Simultaneously FASB also issued SFAS No. 142, which replaced goodwill amortization for impairment tests. In the meantime, IASB also started a business combinations project scheduled in two phases. The first has produced already IFRS 3, issued in March 2004, which also determined the purchase method as the single way for business combinations. The second phase is still in course and will provide guidance about the purchase method application (or ‘acquisition method’, as the board meanwhile decided to rename it). Once again, this topic has proved to be a very fertile ground for discussions, as IASB apparently dropped the ‘fresh start’ application and issued an ED with proposed amendments for the recently published IFRS 3. In the UK, business combinations accounting is still ruled by FRS 6 and FRS 7, which are not aligned with IFRS 3 and further IASB proposals. ASB is monitoring the IASB project and it is very likely to adopt its GAAPs, which means that business combinations accounting in the UK will change very soon. The accounting trend for business combinations seems now clear, but many questions remain, such as, was the pooling of interests method ban a major loss? Which challenges arise from replacement of goodwill amortization for impairment tests? With this paper the authors intend to discuss how and if business combinations accounting uniformity is indeed desirable, highlighting advantages and disadvantages, benefits and eventual problems for professionals and stakeholders. A final note to stress is that this paper deals with uniformity of business combinations accounting and not with international accounting harmonisation, to which we are required to refer since it is inherent to recent developments within this topic.